Rank, strain, and corruption among Chinese public officials: A general strain theory perspective - Wang, Kangqing; Dai, Mengliang; Xia, Yiwei (Frontiers in Psychiatry, 2022)
The problem of corruption has long been a societal focus in China. Agnew’s general strain theory (GST) offers a good explanation of the drive to engage in corruption; that is, offenders are likely to be driven by various types of strains and engage in corrupt behavior as a coping mechanism. However, whether and how an official’s rank moderates the effect of strain on corrupt behavior has yet to be explored. The current study surveyed 687 inmates from 60 prisons in China who had been convicted of corrupt behaviors. The results show that although different levels of officials experience different types of strain, nearly all types of strains are significantly and positively associated with the frequency of corrupt behavior. As for the conditional effect, officials’ ranks significantly moderate the relationship between work-related strain and the frequency of corrupt behavior; that is, work-related strain is shown to have a more significant effect on officials at the clerk level (a higher rank) than on officials at non-clerk level (a lower rank). This research is believed to further expand on the applicability of GST to corruption in non-Western societies.